Mechanisms of Circadian Systems in Animals and Their Clinical Relevance - Aguilar-Roblero, Raúl; Díaz-Muñoz, Mauricio; Fanjul-Moles, Mária Luisa (Springer International Publishing : Imprint: Springer, 2015)
Well known experts in the field of Chronobiology from around the world, provide an integrative view of the state of the art of circadian biology. At present, genetic and epigenetic interaction of regulatory pathways among circadian oscillators, metabolic networks, cellular differentiation and neuronal communication are subject of intense scrutiny. The book is organized in three sections: The first includes selected examples of the circadian systems of crustaceans, insects, fish, birds and mammals. The second is a detailed view of the physiological mechanisms underlying the circadian clocks in mammals. Finally, in the third section some examples of the relevance of circadian biology and circadian misalignment to health and disease are provided including nutrition and metabolism, obesity, cancer, cardiovascular and pulmonary diseases, Huntington and affective diseases. This section concludes with a brief review on gene therapy and its potential use as a therapeutic tool to correct "clock genes" pathologies. This book is aimed at all those interested in contemporary aspects of physiology, biochemistry and molecular biology applied to the study and characterization of timing systems.. It could be used as an initial approach to this field, but it also provides updated information for those already familiar with the fascinating field of Chronobiology.